Legal Capacity of Afghanistan After the Succession of Government by the Taliban - Akbar, Muhammad (Universitas Negeri Gorontalo, 2024)
The purpose of this study is to examine how the legal capacity of Afghanistan after the succession of government by the Taliban. This research uses a normative legal research type with a statutory approach (statute approach) and also a historical approach (historical approach). The research results show thatthe phenomenon that occurs in Afghanistan is the succession of government, so basically the principle used is the principle of continuity, so that even though there are changes internally from the Afghan state in the government system, the country is still bound by rights and obligations according to international law. This is as stated in article 11 of the 1978 Vienna Convention which explains that a change in the government of a country does not affect the boundaries set in the agreement and also the rights and obligations set by an agreement.